12 About the Idea of an Intuitive Didactics and the Role of Intuition in the Activity of Teaching and Learning Assessment - Marius Esi (Association of Social and Educational Innovation, 2014)
A judicious analysis of the intuitive didactics implies, in our opinion, the consideration of the idea of dynamic education. In other words, in so far as in the (trans) international system education can be found different ways to approach the levels of teaching and learning assessment, we can only assume that the idea of intuitive didactics proves to be more than necessary in educational activity. Furthermore, the relevant pragmatic of intuitive didactics becomes obvious in the conditions in which theoretical, acknowledged/ taught contents have a correspondent in social reality. The need of intuitive didactics within educational activity is justified to the extent that educational content recovery involves a resizing of the idea of teaching and learning assessment. In fact, such an undergone approach to a rigorous scientific analysis reveals a number of aspects whose meanings and representations may acquire epistemological legitimacy. But, we consider that such a belief is justified under the conditions in which teaching interest focuses mainly on the idea of change/adaptation.